Breaking the Scroll (BTS): A Randomized Controlled Trial Assessing Social Media Use and Youth Mental Health in the Context of a Developing Economy - Zubaria Andlib (Global Labor Organization (GLO), 2025)
This study examines the causal impact of addictive patterns of social media use on mental health outcomes through a randomized controlled trial conducted among young individuals (18 to 24 years) in Pakistan. Participants in the treatment group received an intervention designed to limit their social media use, while the control group maintained their usual usage patterns. The findings indicate that limiting social media use leads to significant improvements in mental health, including reductions in depression and anxiety, alongside notable increases in self-esteem and overall well-being among young adults. The intervention improves sleep quality and reduces perceived stress, demonstrating that excessive use of social media apps significantly affects psychological and behavioural health. The findings highlight the potential for policy interventions, including behavioural nudges, youth-targeted awareness campaigns, and regulatory actions, to decrease the negative externalities associated with unregulated social media use. Future research should evaluate the long-term effects of addictive patterns of social media use and the differential impacts across diverse socio-demographic groups, considering the increasing integration of digital platforms into everyday life.
Keywords: I12; I31; D91; O33; 330; Social Media; Mental Health; Randomized Controlled Trial; Digital Well-being; Behavioural Nudges